ETUDE DE PRODUCTIVITE DE L’ENTREPRENARIAT D’UNE PETITE ENTREPRISE : CAS DE LA RIZERIE MATER DEI DE 2010 À 2013 - Oseyatoko, Marcel; DIVOVA Christian, Par NALINGAME (IJRDO - Journal of Business Management, 2018)
The entrepreneurial of a small industrial company in RDC in general, and in the town of Isiro in particular following the example rice mill MATER Dei is a profitable activity likely to create incomes with its initiator; ¶and to contribute to the economic development of the country.¶